Comparing the Nurse Work Environment, Job Satisfaction, and Intent to Leave Among Military, Magnet®, Magnet-Aspiring, and Non-Magnet Civilian Hospitals. (June 2022) - Patrician, Patricia A.; Olds, Danielle M.; Breckenridge-Sproat, Sara; Taylor-Clark, Tanekkia; Swiger, Pauline A.; Loan, Lori A.
Abstract : OBJECTIVE: This study aimed to compare the nurse work environment, job satisfaction, and intent to leave (ITL) among military, Magnet ®, Magnet-aspiring, and non-Magnet civilian hospitals. BACKGROUND: The professional nurse work environment is an important, modifiable, organizational trait associated with positive nurse and patient outcomes; creating and maintaining a favorable work environment should be imperative for nursing leaders. METHODS: Secondary data from the Army Nurse Corps and the National Database of Nursing Quality Indicators included the Practice Environment Scale of the Nursing Work Index (PES-NWI) and single-item measures of job satisfaction and ITL. RESULTS: Magnet and military hospitals had identical PES-NWI composite scores; however, statistically significant differences existed among the subscales. Military nurses were the most satisfied among all groups, although this difference was not statistically significant, yet their ITL was highest. CONCLUSIONS: Favorable work environments may exist in other organizational forms besides Magnet; however, the specific components must be considered.